Analysis of the Influence of Financial Ratios on Profitability in Islamic Commercial Banks in the Period 2018-2023 - Aisah Citra Ayu; Syahrul Amsari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to analyze the profitability of Islamic commercial banks from 2018 to 2023 using various financial parameters. The analysis methodology used in this study is multiple linear regression analysis, which is one of the associative quantitative techniques. Using SPSS software, a purposive sampling strategy is used for the sampling procedure. In this study, a total of fifteen Islamic commercial banks became the population, with nine of these institutions being samples that met all the requirements. This study found that between 2018 and 2023, the profitability of Islamic commercial banks was significantly affected simultaneously by the capital adequacy ratio (CAR), non-performing loans (NPF), and financing ratio (FDR) factors on profitability. Profitability in this study was not partially affected by several of these factors.